Barriers to accessing methamphetamine treatment: A systematic review and meta-analysis. (1st November 2016) - Cumming, Craig; Troeung, Lakkhina; Young, Jesse T.; Kelty, Erin; Preen, David B
Highlights: Psychosocial barriers to accessing methamphetamine treatment are most prevalent. The most prevalent barrier was stigma/embarrassment. Methamphetamine services addressing psychosocial barriers are urgently needed. Treatment options for polysubstance use involving methamphetamine are also needed. Abstract: Background: Methamphetamine use is associated with a range of poor health, social and justice outcomes. In many parts of the world increased methamphetamine use has been identified as a major public health concern. Methamphetamine treatment programmes have been effective in reducing and ceasing use, however a range of barriers have prevented these programmes being widely adopted by methamphetamine users. This review examines the barriers to accessing meth/amphetamine treatment identified in the literature. Methods: Databases were systematically searched using relevant terms for peer-reviewed articles describing original research exploring the barriers to accessing treatment for meth/amphetamine use. Reviews and grey literature were excluded. Eleven studies conducted in 5 countries were included in data synthesis; this involved a systematic review of all 11 studies, and meta-analysis of the prevalence of barriers reported in 6 studies that published sufficient quantitative data. Results: Psychosocial/internal barriers to accessing methamphetamine treatment were most prevalent across studies (10/11 studies). Meta-analysis confirmed the four most commonly endorsed barriers to treatment access across studies all psychosocial barriers were embarrassment or stigma (60%, 95% CI: 54–67%); belief that treatment was unnecessary (59%, 95% CI:54–65%); preferring to withdraw alone without assistance (55%, 95% CI:45–65); and privacy concerns (51%, 95% CI:44–59%). Conclusions: The primary barriers to accessing methamphetamine treatment are psychosocial/internal. Services and treatment models that address these barriers are urgently required. There is a growing need for methamphetamine-appropriate treatment services. Further research evaluating treatment engagement and effectiveness for methamphetamine and polysubstance use, including the development of effective pharmacotherapies is warranted.